Redox-responsive mesoporous silica nanoparticles : a physiologically sensitive codelivery vehicle for siRNA and doxorubicin - Ma, Xing (2015)
Aims: Efficient siRNA/drug codelivery carriers can offer great promises to cancer treatment on account of synergistic effect provided from cancer-associated gene and anticancer drugs. In this work, a redox-responsive drug/siRNA codelivery vehicle based on mesoporous silica nanoparticles was fabricated to simultaneously deliver siRNA and doxorubicin (Dox) in vitro and in vivo. Results: The nanoparticle surface was functionalized with the adamantane (AD) units. Formation of stable host–guest complex between disulfide bond linked-AD and ethylenediamine-modified β-cyclodextrin is capable of fully blocking drugs inside the nanopores, while amino groups can complex with siRNA via electrostatic interaction. Relatively high concentration of glutathione in biophysical environment provides natural reducing agent to trigger drug/siRNA release by cleaving pre-introduced disulfide bonds. B-cell lymphoma 2 (Bcl-2) siRNA was codelivered to silence Bcl-2 protein expression in HeLa cells, resulting in enhanced chemotherapy efficacy in vitro. In vivo delivery experiment carried out in transgenic zebrafish larvae indicates that the delivery of Dox inhibits the development of choroid plexus in a dose-dependent manner, leading to successful decrease of green fluorescence protein transcription in choroid plexus. Reduction of liver tumor was also demonstrated after injection of Dox-loaded nanoparticles. Innovation: We successfully demonstrated that functional nanoparticles could serve as an efficient carrier for the delivery of Bcl-2 siRNA and Dox in HeLa cells and in transgenic zebrafish larvae, leading to enhanced therapeutic efficacy. Conclusion: Enhanced cytotoxicity caused by simultaneous delivery of Bcl-2 siRNA and Dox was observed in HeLa cells. Drug-loaded nanoparticles were internalized in vivo, inhibiting the development of choroid plexus and the progression of liver tumor.